The Development and Single-Laboratory Validation of a Method for the Determination of Steroid Residues in Fish and Fish Products. (27th November 2019) - Watson, Lynn; Potter, Ross; Murphy, Cory; Gibbs, Ryan
Abstract: Due to potential use in aquacultured fish products, the Canadian Food Inspection Agency has identified residue testing for steroids as a priority. These compounds are used in aquaculture primarily to direct sexual differentiation with both androgens and estrogens applied depending on the desired outcome. Published research is lacking with respect to steroid residue testing in fish; however, recent studies in other matrixes provided transferable cleanup techniques. A simple, rapid, and sensitive method was developed and validated for use in monitoring aquacultured fish products for the presence of methyltestosterone, nandrolone, epi-nandrolone, boldenone, and epi-boldenone residues. The developed method consists of solvent extraction followed by cleanup using hexane and dual cartridge SPE with analysis by ultra-HPLC-MS/MS. The method is capable of detecting and confirming steroid residue levels ranging from 0.05 to 25 ng/g in salmon and tilapia, depending on the analyte. Recoveries ranged from 88 to 130% for the analytes. Instrument repeatability was less than 13% for all compounds, while intermediate precision ranged from 5 to 25% RSD. HorRat values were within acceptable ranges.